Simplify the expression. 9 – 5(–11x + 7)

Question

Simplify the expression. 9 – 5(–11x + 7)

in progress 0
RuslanHeatt 2 weeks 2021-07-22T07:41:07+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-22T07:42:40+00:00

    Answer:55x-26
    9-5(-11x+7)
    9+55x-35
    55x-26

    0
    2021-07-22T07:42:52+00:00

    Answer:

    5x – 26

    Step-by-step explanation:

    9 – 5(-11x + 7)

    • multiplying both the variables within the parenthesis by 5

    = 9 – (-55x + 35)

    • distributing the minus sign

    = 9+ 5x – 35

    • combining like terms

    = (9 – 35) + 5x

    = -26 + 5x

    • rearranging the terms such that the variable with x come first

    = 5x – 26

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )